2020
DOI: 10.3389/fnins.2020.610898
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrative Nucleoside Transporters-1 Inhibitors Act as Anti-epileptic Agents by Inhibiting Glutamatergic Transmission

Abstract: Background and Purpose: Adenosine dysregulation is associated with the occurrence of the epilepsy and equilibrative nucleoside transporters-1 (ENT-1) functions as an important regulator of extracellular adenosine in the brain. This study was aimed to prove the anti-epileptic effect of BBB permeable ENT-1 inhibitors, JMF1907 and J4, on animal models of various epilepsy, and the mechanisms that are involved.Experimental Approach: Maximal electroshock seizure (MES), pentylenetetrazol (PTZ)-induced seizure and kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
(56 reference statements)
1
10
0
Order By: Relevance
“…It has also been revealed that the expression of ENT1 increased in patients suffering from epilepsy and also in animal models of epilepsy and pharmacological inhibition of ENT1 transporters in epileptic animal models decreased the severity of seizures (Ho et al 2020). Data of the present study revealed that the increased expression of the ENT1 mRNA seen in the kindling model of epilepsy is ameliorated by levetiracetam.…”
Section: Discussionsupporting
confidence: 63%
“…It has also been revealed that the expression of ENT1 increased in patients suffering from epilepsy and also in animal models of epilepsy and pharmacological inhibition of ENT1 transporters in epileptic animal models decreased the severity of seizures (Ho et al 2020). Data of the present study revealed that the increased expression of the ENT1 mRNA seen in the kindling model of epilepsy is ameliorated by levetiracetam.…”
Section: Discussionsupporting
confidence: 63%
“…Adenosine is an inhibitory neuromodulator and has been proposed as an endogenous anticonvulsant molecule [ 73 , 78 ]. An increase in extracellular adenosine and sustained enhancement in adenosine metabolites (including hypoxanthine, xanthine, and inosine) were observed in the brains of epileptic animal models, suggesting a compensatory protective mechanism in response to seizures [ 1 , 111 ]. On the other hand, since A 1 R activation mediates presynaptic inhibition and stabilization of excitatory membrane potential, it has been logically speculated that dysregulation of A 1 R signaling may contribute to epileptogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Direct injection of a specific ENT1 inhibitor, nitrobenzylthioinosine, into the hippocampus ameliorated the severity of seizures and prolonged the onset latency of pilocarpine-induced seizures in rats [ 248 ]. Recently, systemic administration of BBB-permeable ENT1 inhibitors (JMF1907 and J4) produced beneficial effects in various seizure models that represent generalized tonic–clonic seizures, generalized myoclonic seizures, and focal seizure conditions [ 111 ] (Table 2 ). The anti-epileptic effects were associated with the suppression of excitatory neuronal activities by reducing the action potential-dependent release of neurotransmitters [ 111 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting study recently reported that Tau22 mice are more susceptible to pentylenetetrazol (PTZ) for seizure and mortality than WT mice, probably due to the enhanced expression of ADK [ 65 ]. This is of great interest because J4 is an anti-epileptic agent in a PTZ-induced kindling model [ 66 ]. Given that J4 treatment reduced the level of ADK in Tau22 mice (Table 1 ), it is plausible that modulation of ADK may contribute to the beneficial effect of J4 in Tau22 mice.…”
Section: Discussionmentioning
confidence: 99%